Transit Beirut: UNHCR, Diaspora Networks, and the Covert Resettlement of Armenians during the Cold War - Maja Janmyr (Mashriq & Mahjar)
A “most extraordinary” resettlement operation occurred in the 1950s and 1960s, during which thousands of Armenians from Bulgaria and Romania were systematically and discreetly resettled to the United States via Lebanon. This article explores how and why this small Levantine country became central to such a scheme and examines the roles of the United Nations High Commissioner for Refugees (UNHCR) and the broader refugee regime in this resettlement process. Through an archive-based study of the Armenian resettlement scheme, the article foregrounds Beirut as a significant site for the articulation and development of the modern refugee regime. By highlighting the contributions of diaspora organizations such as the Armenian National Committee to Aid Homeless Armenians (ANCHA), it demonstrates the intricate involvement of non-state actors in this regime.